2012
DOI: 10.1159/000336086
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide Therapy via SSTR: Future Aspects from Experimental Animal Studies

Abstract: There is need for better therapeutic options for neuroendocrine tumours. The aim of this review was to summarize results of experimental animal studies and raise ideas for future radionuclide therapy based on high expression of somatostatin (SS) receptors by many neuroendocrine tumours. In summary, one of the major options is individualized treatment for each patient, including choice of SS analogues, radionuclides and treatment schedules. Other options are methods to increase the treatment effect on tumour ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 269 publications
0
20
0
Order By: Relevance
“…The kidneys are one of the major sites of side effects of 177 Lu-octreotate therapy of neuroendocrine tumors due to the high uptake of the radiopharmaceutical in this organ [3], [5], [30][32]. Basic insight into how normal kidney tissue responds to 177 Lu-octreotate exposure is therefore vital for the continued optimization of therapy with this radiopharmaceutical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The kidneys are one of the major sites of side effects of 177 Lu-octreotate therapy of neuroendocrine tumors due to the high uptake of the radiopharmaceutical in this organ [3], [5], [30][32]. Basic insight into how normal kidney tissue responds to 177 Lu-octreotate exposure is therefore vital for the continued optimization of therapy with this radiopharmaceutical.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney cortical tissue should be given extra attention because 177 Lu-octreotate uptake takes place to a somewhat higher extent in this part of the kidney by, e.g., receptor-mediated endocytosis via the megalin/cubulin complex and somatostatin receptors, amino acid/oligopeptide transporters, pinocytosis, and passive diffusion [3], [5], [32]. Furthermore, it has previously been shown that the radioactivity localizes in the proximal tubules of the cortex, with less activity in the distal tubules and glomeruli, as evaluated by micro-autoradiography [3], and 177 Lu-octreotate induced damage has been found in the cortical tissue [4].…”
Section: Discussionmentioning
confidence: 99%
“…GOT1 cells were derived from a liver metastasis and expressed neuroendocrine markers, including somatostatin receptor type 2 (SSTR2). This cell line has been used as a model for optimisation of SSTR2-mediated peptide receptor radionuclide therapy (PRRT) (Kölby et al 2005, Bernhardt et al 2007, Forssell-Aronsson et al 2013, Dalmo et al 2017. More recently, in 2009, three cell lines were established from a patient with metastatic SINET disease (Pfragner et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, treatment with the somatostatin analogue 177 Lu-octreotate has shown promising results [411]. However, few patients achieve complete remission and there is a need for improvement of 177 Lu-octreotate treatment, with some options being (1) increasing the therapeutic effect on tumour tissue or (2) reducing the uptake in healthy organs at risk [12]. By lowering the uptake in organs at risk, the administered activity, and hence the absorbed dose to the tumour, could be increased.…”
Section: Introductionmentioning
confidence: 99%